Cultivation of Ganoderma lucidum (Fr.) Karst. - Dadwal, V. S., Jamaluddin (Indian Forester, 2004)
The extract of the fungus Ganoderma lucidum is used for treatment of joint pains, as elixer of life, good health and well-being. It is commercially cultivated in China, Japan, USA and Malayasia but so far it has not been cultivated in India. It has several host trees species in India and fresh isolates were obtained from infected roots for taking up its cultivation. The results show that spawn and fruit bodies grown on chips and logs of Delonix regia are the best and in them those grown on chips, are still beter. Chips and logs of other species tried gave inferior results.